Ranking Effectiveness of Non-Pharmaceutical Interventions Against COVID-19: A Review (Informatica, 2022)
In this review, we examine 34 studies based on experimental data that estimate and compare the effectiveness of 12 non-pharmaceutical government interventions against Covid-19 based on cases, deaths, and/or transmission rates to assess their overall effectiveness. The studies reviewed are based on daily country-level data and cover 4 to 200 countries and regions worldwide with varying time intervals, spanning the period between December 2019 and August 2021. We found that the overall most effective interventions are restrictions on gatherings, workplace closing, public information campaigns, and school closing, while the least effective are close public transport, contact tracing, and testing policy.